Current trends in Rwanda's HIV/AIDS epidemic. (30th March 2006) - Kayirangwa, E; Hanson, J; Munyakazi, L; Kabeja, A
Abstract : Objective: To review the trajectory of Rwanda's HIV epidemic, including long term trends and more recent trends in HIV prevalence, markers of HIV incidence, and behavioural indicators. Methods: This paper reviews the history of HIV serological and behavioural surveillance efforts in Rwanda, dating back to the early 1980s, synthesising findings from surveillance, research, and other relevant HIV programmatic data. The documentation reviewed includes published findings, conference abstracts, and unpublished analyses. Special emphasis is given to more recent sentinel surveillance results and data collected using known, documented methods. Recent trends in HIV prevalence were assessed among sites participating in the three most recent consecutive rounds of antenatal clinic sentinel surveillance. Results: Early HIV surveillance in Rwanda documented high HIV prevalence in urban areas with HIV widely disseminated into rural areas by 1986. Between 1988 and 1996, HIV prevalence among pregnant women ranged from 21% to 33% in Kigali, from 8% to 22% in other urban settings, and from 2% to 12% in rural settings. More recent surveillance among pregnant women has demonstrated more moderate prevalence, with urban/rural differences narrowing slightly. Between 1998 and 2003, HIV prevalence may have declined in urban areas, whereas rural areas appear to have remained stable. Age at first sexual intercourse is relatively late in Rwanda (20 years for both males and females) and has remained stable since at least 1992. Conclusions: The present analysis suggests that Rwanda may have experienced declines over the long term in HIV prevalence in urban areas, especially in Kigali, and may have stable or slightly rising HIV prevalence in rural areas. The limited behavioural data available suggest that, on the national level, Rwanda may benefit from a unique combination of low numbers of partners and late sexual debut, which may have had a mitigating effect on HIV prevalence.